Pelatihan Blended Learning bagi Guru di Lingkungan Madrasah Tsanawiyah Negeri Sumber Bungur - Subaidi, Agus; Zayyadi, Moh; Hasanah, Sri Indriati; Halim, Durroh (Jurnal Pemberdayaan Masyarakat, 2019)
Not all teachers in Madrasah Tsanawiyah (MTs)’s public of Sumber Bungur have the ability to adapt to Information and Communication of Technology(ICT) development. Especially in the management of technology-based applications.Whereas with the rapid development of technology, teachers ' knowledge of technology must be mastered in order to support success in learning. The goal of this devotion is to introduce blended learning and motivate teachers to apply technology in learning.The participants of the devotion are representatives of the teacher teachers in the subjects at MTs Sumber Bunga as many as 14 people. Before the devotion carried out the participants were given Pretests aims to know the initial knowledge of participants related to the model of learning, utilization of ICT and blended learning, the result teachers are less utilizing ICT in learning and yet Know about blended learning. Whilethe results of the dedication gained data that the participants experienced an increase in knowledge about blended learning. Participants can also utilize the app Edmodo and quiz creator that supports teachers to apply blended learning. The poll stated that participants responded well to the implementation of devotion. They want to apply blended learning in learning after knowing its usefulness.